Corrosion stability of molybdenum and tungsten coatings in lead-bismuth eutectic - Azhazha, V.M.; Bakai, A.S.; Glushko, P.I.; Kovtun, K.V.; Omelchuk, A.A.; Semenov, N.A.; Skryptun, I.N.; Sheremet, V.I.; Shirokov, B.M.; Shmegera, R.S. (Вопросы атомной науки и техники, 2005)
The paper presents results of corrosion tests of tungsten- and molybdenum-based protective coatings, deposited on nickel-molybdenum alloys (hastelloy) in heavy metal melts (Pb, Bi, Pb–Bi eutectic). Results of an investigation of hastelloy samples without protective coating are given for comparison. The investigations were carried out under static conditions at 550 °C. The mechanical properties of the samples under investigation have been shown that the corrosion stability of the uncoated alloys studied decreases in the order: lead – lead-bismuth eutectic – bismuth. The use of protective tungsten and molybdenum coatings ensures corrosion stability of hastalloy with retention of its mechanical properties. Наведено результати дослідження корозійної стійкості нікель-молібденових сплавів (хастелой) в розплавах важких металів (Pb, Bi, Pb-Bi). Корозію вивчено в статичних умовах при температурі 550 °С. Встановлено, що в ряді розплавів свинець – свинець-вісмутова евтектика – вісмут корозійна стійкість вивчених сплавів падає. Показано, що використання захисних покрить з вольфраму та молібдену підвищує корозійну стійкість хастелою. Представлены результаты исследования коррозионной стойкости никель-молибденовых сплавов (хастеллой) в расплавах тяжелых металлов (Pb, Bi, Pb-Bi). Коррозия изучена в статических условиях при температуре 550 °С. Установлено, что в ряду расплавов свинец – свинец-висмутовая эвтектика – висмут коррозионная стойкость изученных сплавов падает. Показано, что использование защитных покрытий из вольфрама и молибдена повышает коррозионную стойкость хастеллоя.